Lack of difference between continuous versus intermittent heparin infusion on maintenance of intra-arterial catheter in postoperative pediatric surgery: a randomized controlled study - Maria Carolina Witkowski; Maria Antonieta P. de Moraes; Cora Maria F. Firpo (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To compare two systems of arterial catheters maintenance in postoperative pediatric surgery using intermittent or continuous infusion of heparin solution and to analyze adverse events related to the site of catheter insertion and the volume of infused heparin solution. METHODS: Randomized control trial with 140 patients selected for continuous infusion group (CIG) and intermittent infusion group (IIG). The variables analyzed were: type of heart disease, permanence time and size of the catheter, insertion site, technique used, volume of heparin solution and adverse events. The descriptive variables were analyzed by Student's t-test and the categorical variables, by chi-square test, being significant p<0.05. RESULTS: The median age was 11 (0-22) months, and 77 (55%) were females. No significant differences between studied variables were found, except for the volume used in CIG (12.0±1.2mL/24 hours) when compared to IIG (5.3±3.5mL/24 hours) with p<0.0003. CONCLUSIONS: The continuous infusion system and the intermittent infusion of heparin solution can be used for intra-arterial catheters maintenance in postoperative pediatric surgery, regardless of patient's clinical and demographic characteristics. Adverse events up to the third postoperative day occurred similarly in both groups. However, the intermittent infusion system usage in underweight children should be considered, due to the lower volume of infused heparin solution [ClinicalTrials.gov Identifier: NCT01097031].